APLIKASI ZAKAT, INFAK, SEDEKAH PADA BAZNAS BATANG HARI: Application;Baznas;Zakat Calculator;PHP;ZIS (Zakat Infaq Sedekah). - Pariyadi; Limia Budiarti, Rike; Della Refpriyani, Mei (JURNAL AKADEMIKA, 2022)
Zakat is maliyah ijtima'iyyah worship which has a very important, strategic, and decisive position both in terms of Islamic teachings and in terms of developing the welfare of the people. zakat, infaq, and alms that come in, and data management carried out through Microsoft Excel will certainly take relatively longer time. In addition, the limited budget for existing funds makes BAZNAS experience problems in managing application. One solution to this problem is the creation of an application for zakat, infaq, and alms. Making this application more leverage than writing all incoming zakat, infaq, and alms data, and managing data through Microsoft Excel will certainly take relatively longer time. This financial integration system was built in four stages, namely requirements analysis, system design, implementation, and system testing with the PHP programming language framework, namely Laravel and PostgreSQL database. The features in this application are zakat calculators, payments, registrations and reports. This application provides added value, namely the management of zakat, infaq, and alms data to be faster and more accurate and is expected to help the performance of BAZNAS officers in Batanghari Regency.